The market for German wine in Singapore - Kissler, Simon (2018)
The goal of this master thesis is to give an overview of the conditions and opportunities of the market for German wines in Singapore. It will show what surrounding conditions, specific regulations, current market situations and future market opportunities there are. First, the basic structures of Singapore will be shown, from an economic, political and cultural point of view. Afterwards, a closer look at the Singaporean food and beverage market will be taken. This will show not only the regulations for food and beverages at the Singaporean market, but also some specific regulations for the market of alcoholic beverages. Subsequently the specifics about this market of alcoholic beverages will be pointed out. The situation of the wine market is then the next and major part of this market analysis. It will be analyzed in depth to find out the framework of conditions for German wine in this market. Singapore is a very interesting and growing wine market and functioning as a business hub in Southeast Asia. It offers great opportunities for German wine in the future and therefore, finally, the German wine on the Singaporean market will be analyzed and described. A market research about the presence of German wine in Singaporean wine selling businesses was conducted and gives an overview of the German wine presence on the market.